Production and Purification of Biodiesel: A Short Review - Achol Aguek Tengteng; Muhammad Faseeh Memon; Wan Nur Aisyah Wan Osman; Shafirah Samsuri (Platform, a Journal of Engineering, 2024)
The exploration of renewable energy alternatives is imperative due to the increasing environmental consequences of fossil fuel energy consumption. The production of Biodiesel from sustainable sources, such as non-edible oil waste and refuse cooking oil, arises as a compelling solution to mitigate environmental degradation. This comprehensive review explores the synthesis and purification processes essential to biodiesel production, emphasising the utilisation of various manufacturing techniques, particularly transesterification, which employs a variety of catalysts and feedstocks. Diverse biodiesel sources are examined, highlighting the environmental benefits and performance metrics. The purification methods employed to improve the quality and efficacy of Biodiesel are also thoroughly discussed. The potential of utilising leftover cooking oil is underscored, as it offers an environmentally responsible alternative and aligns with the principles of a circular economy by minimising the impact on food security and reducing waste. Novel techniques in biodiesel production, such as ultrasonication, one-pot supercritical methanol technology, microwave-assisted transesterification, enzymatic transesterification, and hydrodynamic cavitation, are explored for their potential to optimise and enhance the biodiesel production process. The review concludes with insights into the optimisation of transesterification processes, intending to advance biodiesel production in terms of energy security and environmental sustainability.